2019
DOI: 10.1039/c9cc06506g
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective radical hydroboration of electron-deficient alkenes: synthesis of α-boryl functionalized molecules

Abstract: A radical hydroboration of electron-deficient alkenes was developed for the direct synthesis of diverse α-boryl functionalized molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 41 publications
3
19
0
2
Order By: Relevance
“…In contrast, complex 25 proved chemoselective in hydroboration of benzonitriles in the presence of additives bearing ester, alkene and isonitrile functionalities (Scheme B). Selective addition of HBPin to the cyano group was also observed for cyclohexene‐1‐carbonitrile (Scheme A) . However, as expected due to much less energy barriers for addition of HBPin to aldehydes and ketones, hydroboration of the substrates having formyl and acetyl functionalities was found to be non‐selective.…”
Section: Main Group Metal Catalystssupporting
confidence: 53%
See 1 more Smart Citation
“…In contrast, complex 25 proved chemoselective in hydroboration of benzonitriles in the presence of additives bearing ester, alkene and isonitrile functionalities (Scheme B). Selective addition of HBPin to the cyano group was also observed for cyclohexene‐1‐carbonitrile (Scheme A) . However, as expected due to much less energy barriers for addition of HBPin to aldehydes and ketones, hydroboration of the substrates having formyl and acetyl functionalities was found to be non‐selective.…”
Section: Main Group Metal Catalystssupporting
confidence: 53%
“…Selective addition of HBPin to the cyano group was also observed for cyclohexene-1carbonitrile (Scheme 23A). [58] However, as expected due to much less energy barriers for addition of HBPin to aldehydes and ketones, hydroboration of the substrates having formyl and acetyl functionalities was found to be non-selective. Analogously, hydroboration of phenyl acetylenes was found to be preferable over benzonitriles.…”
Section: Main Group Metal Catalystsmentioning
confidence: 65%
“…The present photocatalytic approach provides a new solution for achieving radical arylborations of alkenes with exclusive regio‐ and diastereoselectivity control . The NHC‐boryl radical selectively added to the α‐carbon of electron‐deficient alkenes, while the aryl component was attached to the β‐carbon. The anti ‐stereochemistry was confirmed by X‐ray crystallographic analysis of compound 6 e .…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, computational studies by Rablen and Zipse revealed that the BDEs of B−H bonds in amine‐ and phosphine‐BH 3 complexes were generally reduced to 94–104 kcal/mol [3a,e] . In addition, NHC‐boryl radicals, pioneered by Fensterbank, Lacôte, Malacria, Curran, [5a] were demonstrated to exhibit diverse reactivity in many valuable transformations, including reductions of xanthates, [5b] alkyl/aryl halides, [5c–e] ketones, [5f] and cyanides, [5g] addition, [5h,6a–c] and tandem cyclizations [6d–e] . Recently, Curran, Taniguchi and Wang realized challenging radical addition trans ‐hydroboration of alkynes with NHC−BH 3 in access to NHC ( E )‐alkenylboranes [7] .…”
Section: Methodsmentioning
confidence: 99%